Solving myopia in real-time decision-making using Petri nets models’ knowledge for service-oriented manufacturing systems - Leitão, Paulo (2010)
This paper introduces a novel approach to the real-time decision-making in service-oriented manufacturing systems, addressing the myopia problem usually presented in such systems. The proposed decision method considers the knowledge extracted from the Petri nets models used to describe the services process behavior, mainly the T-invariants, combined with a multi-criteria function customized according to the system’s particularities and strategies. An experimental laboratorial case study was used to demonstrate the applicability of the proposed real-time decision-making approach in service-oriented manufacturing systems, considering some productivity and energy efficiency criteria.